Mikrofluidika - Noč, Matic (Matrika, 2017)
The article is about microfluidics. Firstly, physics of fluids at the small scale are presented. Further on, a detailed description of the basic components of microfluidic chips and the physics behind is presented - diffusion, electro - osmosis, surface tension. Also included is a description of soft litography, the basic technique for the construction of the microfluidic chips. In the conclusion, examples of microfluidic concepts for practical applications in medical diagnosis, pharmaceutical industry and micro assays are presented.
Keywords: active components; aktivne komponente; aplikacije; applications; construction; hidrodinamika; hydrodynamics; izdelava; microfluidic chips; microfluidics; mikrofluidična vezja; mikrofluidika; pasivne komponente; passive components